2019
DOI: 10.3389/fmicb.2019.02176
|View full text |Cite
|
Sign up to set email alerts
|

SCFAs-Induced GLP-1 Secretion Links the Regulation of Gut Microbiome on Hepatic Lipogenesis in Chickens

Abstract: The impact of gut microbiota and its metabolites on fat metabolism have been widely reported in human and animals. However, the critical mediators and the signal transductions are not well demonstrated. As ovipara, chicken represents a specific case in lipid metabolism that liver is the main site of lipid synthesis. The aim of this study is to elucidate the linkage of gut microbiota and fat synthesis in broiler chickens. The broilers were subjected to dietary treatments of combined probiotics (Animal bifidobac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…Previous studies have reported that propionate would stimulate PYY and GLP-1 secretion from intestinal L cells ( Kaji et al., 2011 ), thereby inhibiting appetite and further reducing fat accumulation in mammals ( Chambers et al., 2015 ; Psichas et al., 2015 ). Our recent study ( Zhang et al., 2019 ) also found propionate induces GLP-1 secretion in cultured intestinal epithelial cells, and GLP-1 suppresses hepatocytic lipogenesis in vitro. The appetite-suppressing peptides might be involved in the inhibition of oral propionate administration on chicken fat deposition, as the average daily feed intake of broilers was significantly reduced.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies have reported that propionate would stimulate PYY and GLP-1 secretion from intestinal L cells ( Kaji et al., 2011 ), thereby inhibiting appetite and further reducing fat accumulation in mammals ( Chambers et al., 2015 ; Psichas et al., 2015 ). Our recent study ( Zhang et al., 2019 ) also found propionate induces GLP-1 secretion in cultured intestinal epithelial cells, and GLP-1 suppresses hepatocytic lipogenesis in vitro. The appetite-suppressing peptides might be involved in the inhibition of oral propionate administration on chicken fat deposition, as the average daily feed intake of broilers was significantly reduced.…”
Section: Discussionmentioning
confidence: 68%
“…Our findings fit well with previous reports in which oral administration or colonic infusion of SP could reduce fat accumulation and weight gain in mice and humans ( Chambers et al., 2015 ; Song et al., 2019 ). Alteration of gut microbiota after dietary treatments has been established to play a key role in regulating fat metabolism ( Wu et al., 2019 ; Zhang et al., 2019 ). To test whether dietary supplementation of SP suppressed chicken fat deposition via gut microbiota, we performed high-throughput sequencing on hypervariable region of the 16S rRNA genes of cecal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that SCFAs produced by the microbiota upregulated the expression of GLP-1 via activation of the MAPK pathway. GLP-1 induced reduction in mRNA expression of the fatty acid synthesis related genes [37][38][39]. Therefore, it is suggested that SCFA production by soy protein intake may be related to a reduction in fatty acid synthesis related gene expression.…”
Section: Discussionmentioning
confidence: 99%
“… 74 C. butyricum supplementation increased GLP-1 secretion from the L cells within the intestinal epithelium, putatively due to increased butyrate production triggering the activation of G-protein-coupled receptors 41 and 43 (GPR41 and GPR43). 20 , 71 , 75 Therefore, modulation of GLP-1 signaling may be a mechanism by which C. butyricum CGMCC 9831 in the gut exerts anti-apoptotic neuroprotection in the model of traumatic brain injury 19 , 38 , 70 ( Figure 4a ). Similarly, in a model of chronic stress-induced depression, C. butyricum CGMCC 9830 administration reversed depression-like behavior, increased levels of hippocampal BDNF, and also increased intestinal levels of GLP-1.…”
Section: Butyricum Supplementation: Mechanisms Of Action and Target Pathwaysmentioning
confidence: 99%